Evaluation of physical, mechanical, and thermal properties of woven kenaf/ bio-epoxy composites - Abare, Alhassan Yakubu; Jawaid, Mohammad; Hamid, Norul Hisham; Bakar, Balkis Fatomer A; Ismail, Ahmad Safwan; Sarmin, Siti Noorbaini; Fouad, Hassan; Midani, Mohamad (Sage Publications, 2023)
The demand for eco-friendly materials in many sectors is due to the age-long usage of synthetic materials, which has so many negative impacts on the environment, high energy consumption, and health concerns. The physical, mechanical, morphological, and thermal properties of woven kenaf fibre reinforced bio-epoxy composites are investigated in this study. The bio-composites were produced utilizing a manual lay-up process with varying fibre loading percentages of 30%, 35%, and 40%. Pure Bio-epoxy composites were also prepared as a reference. Physical, mechanical, morphological, and thermal characteristics were assessed. The density and water absorption of the bio-composites increase as the fibre loading increased. The highest density (1.2559 g/cm3) was shown by 40% fibre loading which also exhibited the highest water absorption of 9.8%. Furthermore, the void content revealed that the pure bio-epoxy has the highest value of 3.16% as compared to kenaf/bio-epoxy composites. The highest tensile strength and Young’s modulus was recorded by 40% fibre loading with 92.47 MPa and 9.18 GPa respectively. Impact properties also show enhancement with the increase in fibre loading, it showed the highest impact strength of 7280.8 J/m2at 40% fibre loading. Scanning electron microscopy (SEM) of the tensile fracture indicates that 40% fibre loading shows better fibre and bio-epoxy inter facial bonding because of its higher strength. The Initial decomposition temperature (IDT) of the bio-composites happens at about 230°C–280°C, and the Final decomposition temperature (FDT) is 540°C–560°C which is lower when compared to the pure bio-epoxy composites of 279°C and 560°C. Kenaf/bio-epoxy composites with 40% fibre loading show the best physical and mechanical and thermal properties. Based on our findings, we believe that our green bio-composites has the potential to be employed in various industries such as automobiles, construction and packaging.